Blockade effect of avian-derived anti-VISTA antibodies on immunosuppressive responses. Issue 1 (31st December 2022) - Lin, Yun-Shih; Hsieh, Shang-Ju; Tsai, Keng-Chang; Cheng, Ming-Hui; Yang, Tz-Wen; Lin, Tsai-Yu; Chang, Fu-Ling; Chiang, Chen-Wei; Chen, Wang-Chuan; Huang, Hsien-Te; Lee, Yu-Ching
Abstract : B7 family members and their receptors have been confirmed to participate in T cell response signaling through the induction of immunosuppressive effects. The V-domain Ig suppressor of T-cell activation (VISTA) is expressed in myeloid cells as well as T lymphocytes and plays a crucial role in immune responses. In this study, the phage display technique was employed to isolate specific antibodies targeting VISTA in chickens. In in vitro experiments, VISTA could trigger the inhibition of T-cell activation through interaction during binding. However, isolated single-chain variable fragments (scFvs) effectively inhibited immune cells from producing exhaustion responses, freeing the T cells in peripheral blood mononuclear cells from inhibition and allowing them to remain activated. In addition, the isolated scFvs can block the interaction between VISTA and the VSIG3 ligand. Further analysis on one scFv VS10 revealed that a significant insertion mutation occurred at the CDR3 of the VH domain compared to the chicken germline sequence. Finally, the complex structures of scFv VS10 and VISTA were simulated using molecular docking, and the interaction produced was analyzed. The experimental results support the applicability of VISTA as a target for immune checkpoints and contribute to explaining geometric structures and properties in chicken antibodies.